Direct Current Distribution Measurement of an Electrolyte-Supported Planar Solid Oxide Fuel Cell under the Rib and Channel by Segmented Electrodes. (2nd June 2015) - Koshiyama, Takahiro; Nakajima, Hironori; Karimata, Takahiro; Kitahara, Tatsumi; Ito, Kohei; Masuda, Soichiro; Ogura, Yusuke; Shimano, Jun
Abstract : In the planar SOFCs, the fuel/oxidant distributions and current collecting resistance cause current and temperature distributions over the electrodes under the separator ribs and flow channels. Optimized design of the separator is hence required to improve the output power and chemical/thermo-mechanical durabilities of practical stacks. To clarify the distributions, we prepare planar cells having three segmented cathodes. Current-voltage characteristics are measured with voltage control using three electric loads to reproduce the electrode potentials of a single cell at around 800°C. We find significantly small in-plane oxygen transport rate under the cathode rib and higher current collecting resistance under the channel. Increased anode rib width gives large overpotential under the rib due to fuel starvation. Finite element modeling supports the above experimental results. We demonstrate an improved separator design of a practical stack, taking advantage of this model. Thereby ca. 17% higher maximum power is given in the finite element simulation.